Histopathological Study of Malignant Neoplasm of Breast of Different Age and Sex Groups In a Tertiary Care Hospital - Nahar, Nazmun; Iqbal, Mohammed; Rahman, Kazi Md Shahidur; Yusuf, Md Abdullah; Iqbal, Shahed; Hossain, Shahana (Journal of Current and Advance Medical Research, 2018)
Background: Various types of female breast cancer associated with rapidly increasing age incidence. Objective: The purpose of the present study was to find out the frequency of different types of malignant neoplasm of breast in different age and sex. Methodology: This cross-sectional study was carried out at the Department of Pathology, Chittagong Medical College, Chittagong, Bangladesh from May 2005 to June 2006. Patients presented with breast lump of different age and sex were subjected to this study. Details gross examination was done followed by H & E staining for histopathological study. Result: A total number of 48 samples were selected after fulfilling the inclusion and exclusion criteria. This present study conducted in 27 specimens out of 48 breast lump. Among these benign and malignant were 21 and 27, respectively. Majority of the malignancy found in age group 41-50 years. Histopathologically Invasive ductal carcinoma was common 81.5%.There was significant association between different age group and type of neoplasm. In relation to sex malignant breast neoplasm was more common in female. Conclusion: In conclusion invasive ductal carcinoma was the commonest lesion of breast. In relation to sex malignant breast neoplasm was more common in female. Journal of Current and Advance Medical Research 2018;5(2):42-44